Analisis Pengaruh Perceived Usefulness dan Perceived Ease of Use terhadap Repurchase Intention - Rahma Detik Kurningsih; Iiz Izmuddin; Asyari; Aidil Alfin (Jurnal Ilmiah Ekonomi Islam, 2025)
As one of the e-commerce platforms with the highest traffic in Indonesia throughout 2023, Shopee continues to strengthen its position amid the growing trend of online shopping. Understanding the factors that drive consumers to make repeat purchases is therefore crucial for maintaining customer loyalty and ensuring platform competitiveness. This study aims to examine the influence of Perceived Usefulness and Perceived Ease of Use on Repurchase Intention among students of the Faculty of Islamic Economics and Business (FEBI), UIN Sjech M. Djamil Djambek Bukittinggi, who actively use the Shopee application. A quantitative approach was employed, utilizing Structural Equation Modeling–Partial Least Squares (SEM-PLS) for data analysis. A total of 180 respondents were selected based on the criteria of having an active Shopee account and having made at least two purchases on the platform. The findings reveal that both Perceived Usefulness and Perceived Ease of Use exert a positive and significant influence on Repurchase Intention. These results underscore that consumers’ perceptions of the usefulness and ease of using the application play a substantial role in shaping their decision to continue purchasing through Shopee.